Pendampingan UMKM Kerajinan Lidi Nipah dan Batik di Desa Kace Timur Kabupaten Bangka - Reniati Reniati; Ari Agung Nugroho; Hengky Veru Purbolakseto (Penerbit Goodwood, 2022)
Purpose: To provide digitalization assistance, provide added value and increase sales turnover of the Deshanda Craft Gallery. Method: The method uses participatory, counseling, mentoring and training. Results: The assistance obtained from the implementation are through training, e-commerce applications, digital promotions. So that it has an impact on increasing business motivation, carrying out marketing of products, increasing turnover and making products increasingly known to the public. Conclusions: community service involves small and medium enterprises of Nipah Sticks and Batik Crafts "Galery Deshanda Craft", which has various business of nipah sticks in the form of ornaments and batik. Nipah sticks are an export commodity from the Province of the Bangka Belitung Islands. Lack of promotion, traditional product sales and unprofessional management, lack of availability of raw materials has caused the Deshanda Craft Gallery to experience various obstacles in its development, it could even be threatened with closure due to the Covid 19 pandemic. Limitations: The limitation of this service is the implementation time.